2022
DOI: 10.1101/2022.07.21.501004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D bioengineered neural tissue generated from patient-derived iPSCs develops time-dependent phenotypes and transcriptional features of Alzheimer’s disease

Abstract: Background Current models to study Alzheimer's disease (AD) include cell cultures and animal models. Human diseases, however, are often poorly reproduced in animal models. Developing techniques to differentiate human brain cells from induced pluripotent stem cells (iPSCs) provides a novel approach to studying AD. Three-dimensional (3D) cultures to model AD are represented by organoids, neurospheroids, and scaffold-based cultures. Methods We developed a 3D bioengineered model of iPSC-derived neural tissue that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Alzheimer's disease (AD) is a progressive neurodegenerative condition marked by the abnormal buildup of amyloid beta (Aβ) plaques, the formation of neurofibrillary tau tangles, and progressive neural degeneration 1 . Along with the hallmarks of the disease, neuronal hyperactivity has been reported in patients, animal models and in patientderived cell cultures [2][3][4][5][6][7][8][9][10][11][12] . Previous studies 13 have found that both sporadic and familial AD patients exhibit increased cortical-hippocampal activity, occurrence of seizures during the early phases of the prodromal stage [14][15][16] and faster cognitive decline in patients that exhibit subclinical epileptiform activity 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a progressive neurodegenerative condition marked by the abnormal buildup of amyloid beta (Aβ) plaques, the formation of neurofibrillary tau tangles, and progressive neural degeneration 1 . Along with the hallmarks of the disease, neuronal hyperactivity has been reported in patients, animal models and in patientderived cell cultures [2][3][4][5][6][7][8][9][10][11][12] . Previous studies 13 have found that both sporadic and familial AD patients exhibit increased cortical-hippocampal activity, occurrence of seizures during the early phases of the prodromal stage [14][15][16] and faster cognitive decline in patients that exhibit subclinical epileptiform activity 17,18 .…”
Section: Introductionmentioning
confidence: 99%